2012
DOI: 10.1007/s12639-011-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective survey of human hydatidosis based on hospital records during the period of 10 years

Abstract: Hydatid cyst is a parasitic infection that is widely seen endemically in the Middle East countries. We studied hydatid cyst pattern in hospitalized adult patients in our hospital from 2000 to 2010. In this study 89 patients, 50 females and 39 males who were diagnosed to have hydatid cyst were evaluated. The mean age of the patients was 37.3 and the mean hospital stay was 10.1 days. The main complaint was abdominal pain (66.2%). The most common localization of cysts was the liver and the most radiological metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Clinical examination revealed that abdominal pain was the most common complaint and was present in 46.4% of the cases. Other most common complaints were dyspnea, cough, abdominal mass, chest pain, icterus, dyspepsia, heart pain, and headache, which was similar to previously studies from Iran 22 . The prevalence rate of human hydatidosis in Iran was reported to be 0.61-2 per 100,000 population 13 and in our study, the prevalence of human hydatidosis in Central Province was 1.16 per 100,000 population.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical examination revealed that abdominal pain was the most common complaint and was present in 46.4% of the cases. Other most common complaints were dyspnea, cough, abdominal mass, chest pain, icterus, dyspepsia, heart pain, and headache, which was similar to previously studies from Iran 22 . The prevalence rate of human hydatidosis in Iran was reported to be 0.61-2 per 100,000 population 13 and in our study, the prevalence of human hydatidosis in Central Province was 1.16 per 100,000 population.…”
Section: Discussionsupporting
confidence: 90%
“…In other studies from Turkey [103] and Italy [99] CE was more prevalent among middle-aged and old patients. Since the 20-40 years people are among the most active age groups of the society, CE can have devastating economic damages [71, 81].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Akhlaghi et al (2009) among 1100 referring to blood transfusion organization in Tehran (capital of Iran), 11.63 % of samples were infected with Hydatid cyst indicating presence of latent hydatid cyst among healthy population in the Iran's Capital. Losses from the hydatid cyst infection are not only involved the animal products and their fertility rates, but also include different costs for diagnosis, disabilities and work absenteeism (Mousavi et al 2012).…”
Section: Introductionmentioning
confidence: 99%